Siri’ di Persimpangan Generasi: Peran dan Makna Nilai Siri’ pada Dewasa Awal Suku Bugis - Handayani, Luluk Dewi; Latief, Raudyatuh Zahra; Muhtadini, Rahmita Laily; Setyani, Alifa Indah (Suksma: Jurnal Psikologi Universitas Sanata Dharma, 2024)
This study aims to explore the meaning of Siri’ for the young adults in the Bugis tribe. This research was conducted using a descriptive phenomenological approach with in-depth interviews with the Bugis community. The participants in this study consisted of 3 people who were all of Bugis descent and were born and raised in the Bugis community. Analysis of the interview transcript data was carried out using the analysis procedure by Moustakas (1994). This study found 8 themes in the meaning of the Siri’ with the essential meaning being the value of Siri’ as shame and self-esteem. The formation of the meaning of Siri’ is based on efforts to maintain the good name of the family, a reflection of women's dignity, the agility and courage of men, and efforts to maintain each other's moral values. Currently, the value of Siri’ in society has been considered to have shifted due to the rapid mindset and development of the times, such as the development of technology and social media which has made people indifferent to the values in their culture